An analysis of selected factors influencing the efficacy of psoriasis therapy - Beniamin O. Grabarek; Jakub Krzaczyński; Barbara Strzałka-Mrozik; Dominika Wcisło-Dziadecka (Termedia Publishing House, 2020)
Psoriasis is a chronic disease characterized by a complex immunopathogenesis of recurrent inflammation of the skin. The course and intensity of the disease depend on many genetic, environmental and behavioural factors. The treatment of psoriasis includes a therapy with ultraviolet radiation, methotrexate, cyclosporine A, keratolytic preparations, tar, anthralin, glucocorticoids, calcineurin inhibitors, retinoids, and vitamin D3 derivatives. A new class of biological drugs (personalized therapy) that was introduced includes cytokine inhibitors, i.e. TNF - etanercept, adalimumab, infliximab, certolizumab pegol, golimumab; IL-12/23 - ustekinumab; IL-17 - secukinumab, ixekizumab, brodalumab. Effective treatment of psoriasis is a challenge. It is an important matter in anti-cytokine therapy to determine the influence of factors such as age, sex, environmental factors, viral and bacterial infections, an occurrence of comorbidities, individual rate of drug metabolism, and pharmacologic interactions of additionally taken drugs. The influence of many different factors translates into obtaining a heterogeneous adequate response to molecularly targeted treatments.